2008
DOI: 10.4049/jimmunol.180.11.7697
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Transglutaminase Activation Modulates Inflammation in Cystic Fibrosis via PPARγ Down-Regulation

Abstract: Cystic fibrosis (CF), the most common life-threatening inherited disease in Caucasians, is due to mutations in the CF transmembrane conductance regulator (CFTR) gene and is characterized by airways chronic inflammation and pulmonary infections. The inflammatory response is not secondary to the pulmonary infections. Indeed, several studies have shown an increased proinflammatory activity in the CF tissues, regardless of bacterial infections, because inflammation is similarly observed in CFTR-defective cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
152
2

Year Published

2009
2009
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(159 citation statements)
references
References 42 publications
5
152
2
Order By: Relevance
“…We have shown that in CF airways high levels of reactive oxygen species (ROS) lead to an increase of TG2 activity, TG2-mediated PPAR␥ cross-linking, ubiquitination, and proteasome degradation, thus driving inflammation (22). Blocking TG2 through specific gene-silencing or TG2 inhibitors increases PPAR␥ protein and reverses inflammation (22). The mechanisms by which the genetic CF defect leads to TG2 up-regulation and inflammation, however, are still unknown.…”
Section: Ystic Fibrosis (Cf)mentioning
confidence: 99%
See 3 more Smart Citations
“…We have shown that in CF airways high levels of reactive oxygen species (ROS) lead to an increase of TG2 activity, TG2-mediated PPAR␥ cross-linking, ubiquitination, and proteasome degradation, thus driving inflammation (22). Blocking TG2 through specific gene-silencing or TG2 inhibitors increases PPAR␥ protein and reverses inflammation (22). The mechanisms by which the genetic CF defect leads to TG2 up-regulation and inflammation, however, are still unknown.…”
Section: Ystic Fibrosis (Cf)mentioning
confidence: 99%
“…We have previously investigated the molecular mechanisms that regulate this "intrinsic" proinflammatory profile and made a link between CFTR-defective function and inflammation (22). We have shown that nasal polyp mucosa from CF patients as well as human CFTR-defective cell lines constitutively up-regulate tissue transglutaminase (TG2), a multifunctional protein expressed in several tissues (25).…”
Section: Ystic Fibrosis (Cf)mentioning
confidence: 99%
See 2 more Smart Citations
“…Increased TGase 2 expression correlates with increased NF-kB activity in breast cancer tissue ). Amplification of NF-kB-mediated signaling activity by TGase 2 appears to be mediated by the depletion of peroxisome proliferator-activated receptor-g, a known inhibitor of NF-kB (Maiuri et al, 2008). Either case of TGase-2-mediated downregulation of inhibitor of NF-kB or peroxisome proliferator-activated receptor-g presents reducing suppressor of inflammatory transcription factors.…”
Section: Introductionmentioning
confidence: 99%